What Can Performance Information Do to Legislators? A Budget‐Decision Experiment with Legislators. (17th February 2017) - Demaj, Labinot
Abstract: Studies on the influence of performance information on budgeting decisions have produced contradictory findings. This article offers a framework of the parliamentary context that links performance information to legislators' budgeting decisions. The framework suggests that the impact on politicians' allocations will differ depending on whether performance information is reflected in the budget proposal, whether the allocation issue concerns a politically difficult trade‐off for the decision maker, and whether information falls into a receptive partisan mind. The experimental study uses 57 actual legislators. The results show that the introduction of performance information into legislators' deliberation process leads to stronger deviations from the status quo allocation. This difference occurs because performance information highlights more clearly the expected consequences of budgetary changes and allows for more pronounced reactions. More informed decisions, however, might make compromise among legislators more difficult because individual positions will become more polarized . Abstract : Related Content:Huissoud (PAR May/June 2017)